Geotechnical foundation conditions of Mesologion swimming pool center - Douveas, N.; Kavadia, D.; Papadopoulou, P. (Bulletin of the Geological Society of Greece, 2007)
Although geotechnical tests are standard and commonly used in determining the foundation type to be applied, in some cases the use ofin-situ tests are essential in order to obtain the correct values needed in the geotechnical calculations. In the case of the foundation of Mesologi Swimming-pool Center, an attempt was made to propose a foundation type, suitable from geotechnical point of view, for sediments that lie very close to the sea! The selection of the most suitable foundation type encloses the examination of several parameters. The subsoil there, consists of soft, fine grained, low plasticity materials, CL to SL with alternations of high plasticity clay layers CH. Additionally, the groundwater level is 0,8 meters under the soil surface, demonstrating constant saturation conditions. The combination of soft subsoil layers quality and the high level of groundwater leads to difficult foundation conditions in relation to immediate and secondary consolidation settlement. Geotechnical calculations and calculations of settlement were performed and the most suitable foundation type was semi-compensated mat foundation.